Physics - Jones, Geoff and Mary Jones (Cambridge ; Cambridge University Press, London, 1993)
A second revised edition of this three-volume resource designed for use in Key Stage 4 GCSE coordinated science courses, updated to match the 1995 national curriculum for science. Includes topics organised into double-page spreads, extension text and questions, illustrations and experimental work